Learning to Expect: Predicting Sounds During Movement Is Related to Sensorimotor Association During Listening - Burgess, Jed D.; Major, Brendan P.; McNeel, Claire; Clark, Gillian M.; Lum, Jarrad A. G.; Enticott, Peter G. (Frontiers in Human Neuroscience, 2019)
Sensory experiences, such as sound, often result from our motor actions. Over time, repeated sound-producing performance can generate sensorimotor associations. However, it is not clear how sensory and motor information are associated. Here, we explore if sensory prediction is associated with the formation of sensorimotor associations during a learning task. We recorded event-related potentials (ERPs) while participants produced index and little finger-swipes on a bespoke device, generating novel sounds. ERPs were also obtained as participants heard those sounds played back. Peak suppression was compared to assess sensory prediction. Additionally, transcranial magnetic stimulation was used during listening to generate finger-motor evoked potentials (MEPs). MEPs were recorded before and after training upon hearing these sounds, and then compared to reveal sensorimotor associations. Finally, we explored the relationship between these components. Results demonstrated that an increased positive-going peak (e.g., P2) and a suppressed negative-going peak (e.g., N2) were recorded during action, revealing some sensory prediction outcomes (P2: p = 0.050, p2 = 0.208; N2: p = 0.001, p2 = 0.474). Increased MEPs were also observed upon hearing congruent compared with incongruent sounds (i.e., associated to a finger), demonstrating precise sensorimotor associations not present before learning (Index finger: p < 0.001, p2 = 0.614; Little finger: p < 0.001, p2 = 0.529). Consistent with our broad hypotheses, a negative association between the MEPs in one finger during listening and ERPs during performance of the other was observed (Index finger MEPs and Fz N1 action ERPs; r = -.655, p = .003). Overall, data suggest predictive mechanisms are associated with fine-tuning of sensorimotor associations.